Information Entropy Squeezing and Non-local Correlation Between a Two-Level Atom and Two-Mode Field Under the Classical Field Effect - Khalil, E. M.; Abdel-Khalek, Sayed; Albogami, Waad; Bouslimi, Jamel; Abo-Dahab, Sayed M.; Besbes, Hatem R. (Frontiers in Physics, 2020)
This paper examines the squeezing on information entropy and entanglement on the basis of a quantum scheme that contains two-mode interaction with time dependence of a two-level atom, including the external field. The proposed model is formulated by eliminating the external field after applying a certain transformation. The dynamics of information entropy squeezing and non-local correlation information for the system Hamiltonian are investigated. The effect of the evolution of the squeezing and entanglement by the classical field are estimated. Based on the results, the obtained dynamic behavior of squeezing and entanglement is controlled using the external field.